Binary Message Passing Decoding of Product Codes Based on Generalized Minimum Distance Decoding : (Invited Paper) - Sheikh, Alireza; Amat, Alexandre Graell i; Liva, Gianluigi (2019 53rd Annual Conference on Information Sciences and Systems (CISS), 2019)
We propose a binary message passing decoding algorithm for product codes based on generalized minimum distance decoding (GMDD) of the component codes, where the last stage of the GMDD makes a decision based on the Hamming distance metric. The proposed algorithm closes half of the gap between conventional iterative bounded distance decoding (iBDD) and turbo product decoding based on the Chase-Pyndiah algorithm, at the expense of some increase in complexity. Furthermore, the proposed algorithm entails only a limited increase in data flow compared to iBDD.